A role for liquid-ordered plasma membrane nanodomains coordinating the unconventional secretory pathway of fibroblast growth factor 2? - Lolicato, Fabio; Nickel, Walter (Frontiers in cell and developmental biology, 2022)
Fibroblast growth factor 2 (FGF2) is a tumor cell survival factor that belongs to a subgroup of extracellular proteins lacking N-terminal signal peptides. Whereas this phenomenon was already recognized in the early 1990s, detailed insights into the molecular mechanisms underlying alternative pathways of protein secretion from eukaryotic cells were obtained only recently. Today, we know about a number of alternative secretory mechanisms, collectively termed unconventional protein secretion (UPS). FGF2 belongs to a subgroup of cargo proteins secreted by direct translocation across the plasma membrane. This feature has been classified as type I UPS and is shared with other unconventionally secreted proteins, such as HIV-Tat and Tau. FGF2 translocation across the membrane is initiated through sequential interactions with the Na,K-ATPase, Tec kinase, and phosphoinositide PI(4,5)P2 at the inner plasma membrane leaflet. Whereas the first two are auxiliary factors of this pathway, the interaction of FGF2 with PI(4,5)P2 triggers the core mechanism of FGF2 membrane translocation. It is based on a lipidic membrane pore that is formed by PI(4,5)P2-induced oligomerization of FGF2. Membrane-inserted FGF2 oligomers are recognized as translocation intermediates that are resolved at the outer plasma membrane leaflet by glypican-1, a heparan sulfate proteoglycan that captures and disassembles FGF2 oligomers on cell surfaces. Here, we discuss recent findings suggesting the molecular machinery mediating FGF2 membrane translocation to be highly organized in liquid-ordered plasma membrane nanodomains, the core process underlying this unusual pathway of protein secretion.
Gesehen am 01.07.2022